PEMBERDAYAAN KARYAWAN HOTEL FOURTEEN ROSES LEGIAN, DALAM PENCEGAHAN PENYAKIT INFEKSI SALURAN NAFAS BAWAH DALAM UPAYA PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS KETIGA: EMPOWERMENT OF FOURTEEN ROSES LEGIAN HOTEL EMPLOYEES, IN PREVENTION OF LOWER RESPIRATORY TRACT INFECTIONS IN AN EFFORT TO ACHIEVE THE THIRD SUSTAINABLE DEVELOPMENT GOALS - Masyeni, Sri; Permana Lestari, Sagung Putri; Wedari, Niti (Universitas Hang Tuah Surabaya, 2025)
The threat of various infectious diseases remains emerge in the world after COVID-19 pandemic. Public health response should be addressed to combating the infectious diseases threat. The community services are an important activity to achieve the third SDGs programme such as the prevention the lower tractus respiratory infection. This community partner was the Fourteen Roses Beach Hotel staff. The activities were training and counselling about the lower tractus respiratory infection. We report an increasing of the partners knowledge of prevention the lower tractus respiratory infection as of 70%. The current community service results will support the achievement of the third SDGs